Immune System Dysregulation During Spaceflight: Potential Countermeasures for Deep Space Exploration Missions - Crucian, Brian E.; Choukèr, Alexander; Simpson, Richard J.; Mehta, Satish; Marshall, Gailen; Smith, Scott M.; Zwart, Sara R.; Heer, Martina; Ponomarev, Sergey; Whitmire, Alexandra; Frippiat, Jean P.; Douglas, Grace L.; et al. (Frontiers in Immunology, 2018)
Recent studies have established that dysregulation of the human immune system and the reactivation of latent herpesviruses persists for the duration of a 6-month orbital spaceflight. It appears certain aspects of adaptive immunity are dysregulated during flight, yet some aspects of innate immunity are heightened. Interaction between adaptive and innate immunity also seems to be altered. Some crews experience persistent hypersensitivity reactions during flight. This phenomenon may, in synergy with extended duration and galactic radiation exposure, increase specific crew clinical risks during deep space exploration missions. The clinical challenge is based upon both the frequency of these phenomena in multiple crewmembers during low earth orbit (LEO) missions and the inability to predict which specific individual crew members will experience these changes. Thus a general countermeasure approach that offers the broadest possible coverage is needed. The vehicles, architecture and mission profiles to enable such voyages are now under development. These include deployment and use of a cis-Lunar station (mid 2020s) with possible Moon surface operations, to be followed by multiple Mars flyby missions, and eventual human Mars surface exploration. Current ISS studies will continue to characterize physiological dysregulation associated with prolonged orbital spaceflight. However, sufficient information exists to begin consideration of both the need for, and nature of, specific immune countermeasures to ensure astronaut health. This article will review relevant in-place operational countermeasures onboard ISS and discuss a myriad of potential immune countermeasures for exploration missions. Discussion points include nutritional supplementation and functional foods, exercise and immunity, pharmacological options, the relationship between bone and immune countermeasures, and vaccination to mitigate herpes (and possibly other) virus risks. As the immune system has sentinel connectivity within every other physiological system, translational effects must be considered for all potential immune countermeasures. Finally, we shall discuss immune countermeasures in the context of their individualized implementation or precision medicine, based on crewmember specific immunological biases.